2014
DOI: 10.15835/nsb.6.2.9287
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Eight Varieties of Onion (<i>Allium cepa</i> L.) Cultivated under Open Field in Tunisia

Abstract: A field experiment was conducted from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…Tere was no signifcant diference (P > 0.05) in days of maturity among the onion varieties (Table 4). Tis result disagrees with the observation of [28] who reported that there were signifcant diferences among eight onion varieties in days of bulb maturity.…”
Section: Growth Parameters and Yield Components Of Onioncontrasting
confidence: 99%
“…Tere was no signifcant diference (P > 0.05) in days of maturity among the onion varieties (Table 4). Tis result disagrees with the observation of [28] who reported that there were signifcant diferences among eight onion varieties in days of bulb maturity.…”
Section: Growth Parameters and Yield Components Of Onioncontrasting
confidence: 99%